Study on the lower limits of petrophysical parameters of the Upper Paleozoic tight sandstone gas reservoirs in the Ordos Basin, China - Huiying Cui (Journal of Natural Gas Geoscience, 2017)
There hasn't been a clear understanding of the lower limits of petrophysical parameters of tight sandstone gas reservoirs so far. However, it is an important question directly related to exploration and development strategies. Research methods of the lower limits of petrophysical parameters are reviewed. The new minimum flow pore throat radius method is used to determine the lower limit of flow pore throat radius. The relative permeability curve method, irreducible water saturation method, and testing method, are used to determine the lower limits of porosity, permeability, and gas saturation. After the comprehensive analysis, the lower limits of petrophysical parameters of the Upper Paleozoic tight sandstone gas reservoirs in Ordos Basin are thought as follows: the minimum flow pore throat radius is 0.02 μm, the lower limits of porosity are 3%, the permeability is 0.02 × 10−3 μm2 and the gas saturation is 20%. Besides, the influence of formation pressure on porosity and permeability, the tight sandstone gas filling mechanism, and reservoir characterization petrophysical parameters of tight sandstone reservoirs are further discussed.